Induction of endothelial cell proliferation and von Willebrand factor expression and secretion by leukemic plasma of patients with chronic lymphocytic leukemia before and after inhibition of NF-κB. Issue 6 (September 2016) - Shahidi, Minoo; Mohsen Razavi, Seyed; Hayat, Parisa
Abstract : Although certain evidence has indicated a role for angiogenesis in the pathophysiology of hematopoietic malignancies, its role in chronic lymphocytic leukemia (CLL) prognosis is yet to be defined. To our knowledge, the effects of CLL plasma on cell culture have not been addressed. Therefore, we investigated the effects of CLL plasma on cell cycle regulation and von Willebrand factor (vWF) secretion, and expression in human umbilical vein endothelial cell cultures (HUVECs). Since nuclear factor–kappa B (NF-κB) transcription factor has been a therapeutic target for treatment of cancer, we inhibited NF-κB using small interfering RNA to clarify if there is a role for this factor in probable effects. The cells were treated with the plasma of patients with CLL. Subsequently, cell cycle phase distribution, vWF secretion, expression, and storage were detected using ELISA, flow cytometry, and immunohistochemical staining. In addition, NF-κB was inhibited using small interfering RNA. Plasma treatment promoted cell cycle progression by decreasing the cell number in G1 phase, while increasing the cell number in S phase and G2M phase. A significant increase of vWF expression, secretion, and storage was found, associated with the vWF levels of patients' plasma. We found that induction of cell cycle promotion, but not vWF expression and secretion, was partially suppressed by this inhibition. We found that endothelial cell cycle and vWF expression and secretion affected by CLL plasma and NF-κB play a role in the former. These findings would be useful for understanding the prognostic importance of plasma angiogenic factor levels in CLL.